Optimal Cost of a Solar Photovoltaic System for a Remote House in Bihar - Jha, Sujit Kumar (International Journal of Renewable Energy Development, 2015)
Energy plays a vital role for the growth of a country. Solar energy is the most important renewable energy resources that can play vital role in the replacement of fossil resources to generate clean energy. Due to technological developments in solar power technologies, solar energy can be used for cooling, heating, and daily electricity demand of the world and emerged as viable alternative to produce clean energy in future. The paper describes the technological development of PV model, its present status and future opportunities in the context of Bihar, India. The study was carried out in Bihar, global solar radiation data is required for the calculation and assessment of the working principles of PV system installed at remotely located house to provide adequate power backup. The case study has been based on the solar radiation data available in Bihar, India, the cost of a suitable PV model for a house has been computed based on the analysis of power requirement of a houses in a day.